U.S. national debate topic, 2015-2016. Surveillance - H.W. Wilson Company (Amenia, New York : Grey House Publishing, 2015)
Examines the National Forensic League's 2015/16 Policy Debate, which answers the question: "Should the United States substantially curtail domestic surveillance?" From Edward Snowden's controversial NSA leaks to ongoing arguments regarding domestic surveillance drones and police body cameras, the topic of government surveillance on U.S. citizens is thoroughly explored in this volume. Articles investigate such key issues as the legality of domestic surveillance, the right to privacy-and to what extent citizens can expect privacy in the digital age and in the context of the "war on terror"-as well as the relative effectiveness of the program in counter-terrorism efforts and matters of national security. Articles also weigh the economic costs of the program to federal and local governments and uncover the history of domestic surveillance and how it has evolved over time in light of complex developments in both international relations and technology.--Provided by publisher
1. National security versus personal privacy. The digital invasion: privacy versus secrecy in the digital age -- NSA spying: it didn't start with 9/11 / Jack Kenny -- US Privacy Board dissenters defend balancing act of NSA surveillance / Spencer Ackerman -- Privacy watchdog says NSA spying legal, effective / Tom Risen -- Privacy advocates say NSA reform doesn't require "technological magic" / Sara Sorcher -- Personal privacy is only one of the costs of NSA surveillance / Kim Zetter -- U.S. spy agency reports improper surveillance of Americans / David Lerman -- NSA sued by Wikimedia, rights groups over mass surveillance / David Ingram -- The new surveillance normal: NSA and corporate surveillance in the age of global capitalism / David H. Price -- 2. Legislation and policy. The politics of surveillance: a brief history -- The business of surveillance / Heidi Boghosian -- N.S.A. latest: the secret history of domestic surveillance / John Cassidy -- Scholars explain failures in oversight of domestic spying / Beth McMurtrie -- A new legal theory for the age of mass surveillance / Michael Phillips -- Newly revealed NSA program (CREACH) extends NSA's reach even further / Nadia Kayyali -- Who can control N.S.A. surveillance? / Mattathias Schwartz -- Administration highlights surveillance reforms / Josh Gerstein -- How big business is helping expand NSA surveillance, Snowden be damned / Lee Fang -- 3. Technology. Big brother tech: the technology of mass surveillance and privacy -- New surveillance technology can track everyone in an area for several hours at a time / Craig Timberg -- Domestic drone bills seek to protect privacy rights / Preston Maddock -- Will police body cameras usher in a new surveillance regime? / Gerry Bello -- It costs the government just 6.5 cents an hour to spy on you / Drew F. Cohen -- Visit the wrong website, and the FBI could end up in your computer / Kevin Poulsen -- Silicon Valley's surveillance cure-all: transparency / Joshua Kopstein -- In surveillance debate, White House turns its focus to Silicon Valley / David E. Sanger -- Obama heads to tech security talks amid tensions / David E. Sanger and Nicole Perlroth -- 4. Effectiveness of domestic surveillance in fighting crime and terror. Evaluating federal surveillance programs: a difficult task -- The whole haystack / Mattathias Schwartz -- The militarization of domestic surveillance is everyone's problem / Michael German -- Uncle Sam's databases of suspicion / Hina Shamsi and Matthew Harwood -- ISIS online: a pretext for cyber COINTELPRO? / Eric Draitser -- The FBI keeps arresting hapless jihadi fanboys and calling them ISIS recruits / John Knefel -- What guilty verdict in Silk Road trial might mean for internet freedom / Cristina Maza -- 5. Racial, ethnic, and political profiling. Who to watch?: racial, ethnic, and political profiling in surveillance -- Racial profiling reported in NSA, FBI surveillance /Tom Risen -- Spying on Occupy activists: how cops and Homeland Security help Wall Street / Matthew Rothschild -- The history of surveillance and the black community / Nadia Kayyali -- A racial "big brother" debacle: why is the government spying on Black Lives Matter protests? / Heather Digby Parton -- Black America's state of surveillance / Malkia Amala Cyril.
Series previously published by H. W. Wilson, a division of EBSCO Information Services.
Includes bibliographical references and index.
Keywords: United States. -- National Security Agency/Central Security Service; Electronic surveillance -- Government policy -- United States; Government information -- Access control -- United States; Privacy, Right of -- United States; Police patrol -- United States -- Surveillance operations